On the Issue of Coordinating the Objectives and Instruments of Financial and Monetary Policies - A. G. Siluanov (Мир новой экономики, 2024)
The relevance of the issue of mutual influence of the goals and instruments of financial and monetary policy increases during periods of economic instability. External and internal macroeconomic shocks can undermine the financial stability of the state and have a negative impact on both price and financial stability. In this regard, there is a need to adjust both financial and monetary policies based on harmonization of the instruments of financial and monetary regulation.   The purpose of this study is to develop the theoretical, methodological and applied foundations for coordinating the goals and instruments of monetary and financial policies.   The article concludes with the results obtained in the course of the research.